Effect of group and individualized instruction on achievement scores of three ability groups in sixth grade science - Bautista, Evelyn Pidot 1949- (1978)
This study was conducted to compare the effects of grouped and individualized instruction on achievement scores of pupils in three ability groups who studied a unit on pollution and conservation. The subject consisted of 30 matched pairs of sixth grade pupils of San Quintin Central School in Pangasinan during the school year 1977-1978. They were equally matched into the two treatments according to their IQ levels in the Philippine Mental Ability Tests (Intermediate Exam) and their first semester descriptive ratings in elementary science. There was a significant difference between the science achievement scores of pupils taught by group and individualized instruction in sixth grade science. But the achievement scores of the pupils in high ability group as well as the low ability group did not differ significantly.